Development of intelligent packaging from xyloglucan-chitosan modified film with betalains from dragon fruit (Hylocereus undatus) peels - Lasuardi Permana; Pongsert Sriprom; Woatthichai Narkrugsa; Kanjana Manamoongmongkol; Pornsawan Assawasaengrat (Future Foods, 2025)
• Xyloglucan-chitosan-betalain film acts as a smart freshness indicator. • FTIR and zeta potential confirm ionic and hydrogen bonding in XC-EB complex. • XC-EB film excels as a freshness indicator with good physical/antimicrobial traits. • Modified films detect ammonia, effectively indicating shrimp spoilage. This study aimed to develop intelligent packaging films by, incorporating extracted betalain (EB) from dragon fruit peel into a tamarind seed kernel xyloglucan and chitosan blend (XC). The film were comprehensively characterized for their chemical, physical, mechanical, antimicrobial, and functional properties. Zeta potential and Fourier transform infrared (FTIR) spectroscopy confirmed that the interaction between xyloglucan, chitosan, and betalain were governed by ionic interactions and hydrogen bonding, which stabilized the colloidal network and influenced film microstructure. Increasing betalain concentration enhance film thickness and color intensity with scanning electron microscopy (SEM) revealing uniform surface morphology. Mechanical testing demonstrated that film with a 1:5 (w/v) EB:EC ratio achieved optimal performance balancing tensile strength (22.35 ± 2.25 MPa) and an elongation at break (185.07 ± 4.42 %). The films exhibited suitable barrier properties, with water vapor transmission rate (WVTR) and water vapor peameability (WVP) aligning with food packaging requirements. Antimicrobial assay revealed good activity against Escherichia coli and Staphylococcus aureus, while ammonia sensitivity test demonstrated the ability of film to detect spoilage via visible colorimetric shifts, correlating with total volatile base nitrogen (TVB-N) levels in shrimp. This study highlight the potential of XC-EB films as sustainable, intelligent packaging solutions for monitoring the protein-rich food freshness, leveraging agricultural byproduct to enhance food safety and reduce waste.
Keywords: Botanical Research and Applications; Polysaccharides Composition and Applications; Microencapsulation and Drying Processes